Case report: Giant lymph node metastases: a new opportunity for cancer radioimmunotherapy? - Bian, Yuan; Zhang, Zhenhua; Deng, Xiangyu; Wen, Qinglian; Li, Dan (Frontiers in Immunology, 2024)
Background: Despite the significant progress made in radiotherapy and chemotherapy for the treatment of cervical cancer, patients with lymph node metastasis still have a poor prognosis. It is widely accepted that lymph node metastasis plays a crucial role in the spread of cancer to other organs and is considered an independent factor in predicting a poor prognosis. However, recent research suggests that the importance of lymph nodes in tumor therapy needs to be reevaluated, as preserving the integrity of lymph nodes before immunotherapy can enhance treatment effectiveness. Case Presentation: In this report, we present two cases of advanced cervical cancer patients with giant metastatic lymph node lesions in the neck. These patients were effectively treated with a combination of local radiotherapy and immunotherapy after conventional chemoradiotherapy had failed. The combination therapy resulted in significant clinical improvements, with patient 1 achieving over 12 months of progression-free survival (PFS) and patient 2 maintaining sustained remission for an impressive 24 months.The combination of local radiotherapy and immunotherapy shows promise as a viable treatment option for cervical cancer patients with distant lymph node metastasis, and the giant lymph node metastases may play an important role in this process, which might provide a new opportunity for cancer radioimmunotherapy.